Authentic assessment activities for oral Malay language skills in primary schools - Ramlan, Norliza; Wan Mohammad, Wan Muna Ruzanna; Mahamod, Zamri (International Journal of Evaluation and Research in Education (IJERE), 2025)
The quality of assessment conducted by teachers plays an important role in ensuring students’ mastery of Malay language skills, particularly oral skills. Assessment through direct activities can highlight students’ true potential and skills. Therefore, this study aims to explore the forms of authentic assessment activities for Malay language oral skills in primary schools in Malaysia. The study design is qualitative, using a case study method involving one case across multiple locations. This study involves five Malay language teachers as study participants from five primary schools located in five different states in Malaysia. The research methods used include interviews, observations, and document analysis. The study findings were analyzed thematically using Nvivo14 software. The results of the study identified seven forms of authentic assessment activities implemented by Malay language teachers: role-playing, storytelling, stimulus materials, questioning, edutainment, presentations, and language games. Interview interpretations are supported by observation and document analysis results, which prove that teachers conduct various forms of authentic assessment activities as the best alternative assessments for evaluating primary school students’ Malay language oral skills. Authentic assessment focuses on engaging and realistic activities to facilitate teachers in directly observing students' language development and skills.